EFEKTIVITAS EKSTRAK ETANOL DAUN KENIKIR (Cosmos caudatus) TERHADAP KADAR GLUKOSA DARAH PUASA PADA TIKUS WISTAR YANG DIINDUKSI ALOKSAN - Siti Aissah (2022)
Elevated blood glucose levels are a common symptom in diabetes mellitus from a group of metabolic diseases. DM management can be done with pharmacological, non-pharmacological and alternative therapies, namely the provision of herbal medicines. This study aims to determine the effectiveness of kenikir leaves (Cosmos caudatus) ethanol extract on FBG level of Wistar rats alloxan-induced. The type of this research is a true experiment study with a pre-post test only control group design method, with a sample of 30 male Wistar white rats, weighing 150-200 g, 2-3 month of age, divided into K1 group feed and aquades, K2 group alloxan dose of 125mg/kgBW, K3 group alloxan-induced and given metformin dose of 45mg/kgBW, and P1, P2, P3 group with alloxan-induced and given extract kenikir leaves doses of 150, 300, 600 mg/kg were given for 14 days, then FBG level was checked using a glucometer. The results of the Paired Samples T and One Way Anova test showed a decrease in FBG level givin kenikir leaf extract (p<0,05). The results of the Post Hoc Bonferroni test in the kenikir leaf extract group at doses of 150, 300, and 600 mg/kgBW could reduce blood glucose levels similar to that of metformin (p>0,05). The results of this study found that kenikir leaf extract at a dose of 300 mg/kg can reduce blood glucose levels by 75.63%, so that the dose was the most effective dose in decreasing FBG level on wistar rats alloxan-induced.